Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3906/zoo-1312-44
|View full text |Cite
|
Sign up to set email alerts
|

Identification key for chewing lice (Phthiraptera: Amblycera, Ischnocera)infesting the Indian Peafowl (Pavo cristatus) with one new country record andnew host record for Saudi Arabia

Abstract: The amblyceran and ischnoceran lice removed from the Indian Peafowl (Pavo cristatus L.) collected at the Riyadh bird market, and other specimens available in the King Saud University Museum of Arthropods, Kingdom of Saudi Arabia, were identified. Amyrsidea minuta Emerson, a new country record, and Goniodes dissimilis Denny were found infesting the Indian Peafowl in Saudi Arabia. Goniodes dissimilis is recorded for the first time from this bird species, along with Menacanthus stramineus (Nitzsch), the wellknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Little is known about the ectoparasites of the large number of marine birds of the Arabian Peninsula (Negm et al 2013;Nasser et al 2015). The Suliformes, which form one of the most important components of marine ecosystems, especially for tropical seas, include the interesting endemic Socotra cormorant (Causey & Padula 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the ectoparasites of the large number of marine birds of the Arabian Peninsula (Negm et al 2013;Nasser et al 2015). The Suliformes, which form one of the most important components of marine ecosystems, especially for tropical seas, include the interesting endemic Socotra cormorant (Causey & Padula 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The chewing lice of the Kingdom of Saudi Arabia (KSA) have recently received attention after a decade of neglect (El-Ahmed et al 2012;Al-Ahmed et al 2014;Nasser et al 2015), but these efforts should be viewed as preliminary, considering the notable diversity of these ectoparasitic insects of the region. With more than 4 000 species worldwide, the chewing lice form one of the most diverse orders of parasitic Hexapoda (Price et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The lice were identified based on morphological key described by Price et al (2003); Wall et al (2001);Nasser et al (2014). Collected species have been deposited in the Laboratory of Parasitology, Faculty of Veterinary Medicine, Universitas Airlangga PSDKU Banyuwangi.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted in domestic ornamental birds in Chile reported that peacocks have two species of lice: Goniodes pavonis and Amrysidea minuta . In another study, conducted in Saudi Arabia, it was reported that 13 species of chewing lice parasitize the Indian peacock: six species in three genera of Amblycera and seven species in three genera of Ischnocera …”
Section: Introductionmentioning
confidence: 99%